2021
DOI: 10.1149/1945-7111/ac0062
|View full text |Cite
|
Sign up to set email alerts
|

Potential Dependent Mn Oxidation and Its Role in Passivation of Ni38Fe20Cr22Mn10Co10Multi-Principal Element Alloy Using Multi-Element Resolved Atomic Emission Spectroelectrochemistry

Abstract: The identity of passivating oxides on multi-principal element alloys is of great interest as their optimization offers the potential for exceptional corrosion resistance in aqueous solutions over a broad range of potential and pH. This study focuses on a non-equiatomic Ni38Fe20Cr22Mn10Co10 solid solution alloy and tracks the fate of each alloying element during linear sweep voltammetry, low and intermediate potential holds in the passive potential domain as well as during open circuit relaxation after anodic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 64 publications
(126 reference statements)
1
15
0
Order By: Relevance
“…Noticeable contribution of Mn to the oxide layer was confirmed using XPS analysis in both the studies mentioned above. [82,83] Nevertheless, incongruent dissolution and selective enrichment of Cr were observed in both the cases mentioned above, similar to Cr-containing conventional alloys. Although the passivity of these alloys was attributed primarily to Cr, thermodynamic predictions suggested the formation of complex spinel oxides.…”
Section: Multi-principal Element Alloysmentioning
confidence: 62%
See 2 more Smart Citations
“…Noticeable contribution of Mn to the oxide layer was confirmed using XPS analysis in both the studies mentioned above. [82,83] Nevertheless, incongruent dissolution and selective enrichment of Cr were observed in both the cases mentioned above, similar to Cr-containing conventional alloys. Although the passivity of these alloys was attributed primarily to Cr, thermodynamic predictions suggested the formation of complex spinel oxides.…”
Section: Multi-principal Element Alloysmentioning
confidence: 62%
“…Based on the dissolution profiles and XPS results, the relatively poor corrosion performance was attributed to higher Mn content in the MPEA. To shed more light on the fate of Mn, Han et al [83] studied the dissolution behavior of Ni 38 Fe 20 Cr 22 Mn 10 Co 10 in 0.1 M NaCl (pH ∼ 4). They reported that both Cr and Mn enrichment occurred during active to passive transition, reflecting that Mn contributes to the surface film.…”
Section: Multi-principal Element Alloysmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In the passive film, Mn may be also present given that the dissolution behavior reached a quasi-steady state for t > 5000 s. However, such a film would not be stable as the Mn dissolution rate was higher than other alloying elements and did not show a decaying profile with time, similar to the previously observed case for the same MPEA at pH = 4.0 in 0.1 M NaCl. 34,35 It should also be noted that no potential dependent oscillation was observed for all elemental dissolution rates during AESEC-EIS at 0.60 V vs SCE, different from that at E oc shown in Fig. 5.…”
Section: ′ and Jmentioning
confidence: 73%
“…[27][28][29][30] Atomic emission spectroelectrochemistry (AESEC) has demonstrated to be a powerful technique to track the fate of each alloying elements for MPEAs during electrochemical measurements. 21,[31][32][33][34][35] The fate of each element, whether in metal, oxide or solution during spontaneous dissolution, activation and passivation, was ascertained by the AESEC technique. AESEC enables the determination of atoms which are oxidized but not dissolve in solution, i.e., may have reached the surface as an oxidized insoluble species, via AESEC mass-charge balance.…”
mentioning
confidence: 99%